Body Posture Asymmetry in Prematurely Born Children at Six Years of Age - Zajkiewicz, Katarzyna; Perenc, Lidia; Piwoński, Paweł; Rachwał, Maciej; Drzał-Grabiec, Justyna; Walicka-Cupryś, Katarzyna; Przygoda, Łukasz (BioMed research international, 2017)
Aims. The purpose of the study was to assess body posture asymmetries in the standing and sitting position in prematurely born children at six years of age. Study Design and Subjects. We measured trunk symmetry in coronal plane. The study was carried out in a group of 101 children, aged 6-7 years, mean age of 6.63, including 50 preterm children born at gestational age <32 weeks (preterm group) and 51 full-term children (control group). Outcome Measures. Trunk symmetry in coronal plane was measured using photogrammetric technique with Mora 4G CQ Elektronik. The subjects were examined in standing and sitting position. Statistical analyses were carried out using Shapiro-Wilk W-test, Student’s t-test, Mann–Whitney U test, and Pearson’s chi-squared test. Statistical significance was assumed at p<0.05. Results. No significant differences were found between the groups in the asymmetries identified in the relevant anthropometric points, relative to the position assumed during the examination or to the subjects’ sex. Conclusions. There are no significant differences in body posture in the coronal plane, between preterm children and full-term children. Premature birth does not have adverse effects related to body posture asymmetry in preterm children at the age of six.